Fluorescence Intensity Fluctuation Analysis of Protein Oligomerization in Cell Membranes. Issue 3 (21st March 2022) - Killeen, Tom D.; Rahman, Sadia; Badu, Dammar N.; Biener, Gabriel; Stoneman, Michael R.; Raicu, Valerică
Abstract: Fluorescence fluctuation spectroscopy (FFS) encompasses a bevy of techniques that involve analyzing fluorescence intensity fluctuations occurring due to fluorescently labeled molecules diffusing in and out of a microscope's focal region. Statistical analysis of these fluctuations may reveal the oligomerization (i.e., association) state of said molecules. We have recently developed a new FFS‐based method, termed Two‐Dimensional Fluorescence Intensity Fluctuation (2D FIF) spectrometry, which provides quantitative information on the size and stability of protein oligomers as a function of receptor concentration. This article describes protocols for employing FIF spectrometry to quantify the oligomerization of a membrane protein of interest, with specific instructions regarding cell preparation, image acquisition, and analysis of images given in detail. Application of the FIF Spectrometry Suite, a software package designed for applying FIF analysis on fluorescence images, is emphasized in the protocol. Also discussed in detail is the identification, removal, and/or analysis of inhomogeneous regions of the membrane that appear as bright spots. The 2D FIF approach is particularly suited to assess the effects of agonists and antagonists on the oligomeric size of membrane receptors of interest. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of live cells expressing protein constructs Basic Protocol 2 : Image acquisition and noise correction Basic Protocol 3 : Drawing and segmenting regions of interest Basic Protocol 4 : Calculating the molecular brightness and concentration of individual image segments Basic Protocol 5 : Combining data subsets using a manual procedure (Optional) Alternate Protocol 1 : Combining data subsets using the advanced FIF spectrometry suite (Optional; alternative to Basic Protocol 5) Basic Protocol 6 : Performing meta‐analysis of brightness spectrograms Alternate Protocol 2 : Performing meta‐analysis of brightness spectrograms (alternative to Basic Protocol 6) Basic Protocol 7 : Spot extraction and analysis using a manual procedure or by writing a program (Optional) Alternate Protocol 3 : Automated spot extraction and analysis (Optional; alternative to Protocol 7) Support Protocol : Monomeric brightness determination